Reconstruction of attached soft tissue around dental implants by acelluar dermal matrix grafts and resin splint - Liu, Changying (Int J Clin Exp Med, 2014)
Objectives: The purpose of this study was to recommend a new method using acellular dermal matrix graft and resin splint to reconstruct the attached soft tissue around dental implants in patients with maxillofacial defects. Materials and methods: Total 8 patients (3 male and 5 female patients) diagnosed with maxillofacial defects and dentition defects caused by tumors, fractures or edentulous jaw, were selected for this study. Dental implants were routinely implanted at the edentulous area. Acellular dermal matrix heterografts and resin splint were used to increase the attached soft tissue. The width of attached gingiva in the labial or buccal surface at edentulous area was measured before surgical procedures and after the completion of superstructures. Paired t-test was applied to assess the change of quantitative variables. All tests were 2-tailed, and P < 0.05 was considered statistically significant. Results: The dense connective tissue around implants could be reconstructed one month after the completion of surgical procedures, and the epithelial cuff around the implant neck established very well. The width of attached gingival tissue in the patients increased significantly from a mean of 0.61 ± 0.75 mm to 6.25 ± 1.04 mm. The patients were fully satisfied with the esthetic and functional results achieved. Conclusions: The acellular dermal matrix graft could be used to increase the attached gingiva around dental implants in these patients with maxillofacial defects. The resin splint could facilitate the healing of graft.